2022
DOI: 10.1172/jci160194
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal neoplasia: carcinogenic interaction between bile acids and Helicobacter pylori in the stomach

Abstract: Bile acids modulate cell functions in health and disease, however, the mechanisms underlying their actions on neoplastic cells in the gastrointestinal (GI) tract remain largely unknown. In this issue of the JCI , Noto et al. comprehensively analyzed how interactions between Helicobacter pylori infection, iron deficiency, and bile acids modulate gastric inflammation and carcinogenesis. The investigators used sophisticated models, including INS-GAS mice with elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…6). Although amino acids are mostly reported to play a positive role in immunomodulation, the excessive amino acid accumulation in the present study may promote the colonization of Helicobacter , which is often reported to be a carcinogenic bacterium in the gastrointestinal tract; 33 it has been found that Helicobacter can use amino acids as a sole source of carbon energy. 34 Some studies have suggested that the gut microbiota can absorb amino acids and convert them into bacterial metabolites that create immune problems, such as higher concentrations of cysteine, which produce large a amount of H 2 S, which can inhibit mitochondrial respiration and thus the oxidation of SCFAs.…”
Section: Discussionmentioning
confidence: 54%
“…6). Although amino acids are mostly reported to play a positive role in immunomodulation, the excessive amino acid accumulation in the present study may promote the colonization of Helicobacter , which is often reported to be a carcinogenic bacterium in the gastrointestinal tract; 33 it has been found that Helicobacter can use amino acids as a sole source of carbon energy. 34 Some studies have suggested that the gut microbiota can absorb amino acids and convert them into bacterial metabolites that create immune problems, such as higher concentrations of cysteine, which produce large a amount of H 2 S, which can inhibit mitochondrial respiration and thus the oxidation of SCFAs.…”
Section: Discussionmentioning
confidence: 54%
“…To the best of our knowledge, we did not find any direct or indirect correlation among these bacteria ( Candidatus_Saccharimonas, Candidatus_Actinomarina, Mucispirillum , and Helicobacter ) and OGA/OGT and O-GlcNAc. But we found a couple of flora that were associated with SCFAs ( Wang et al, 2020 ; Gu et al, 2021 ; Liu Q. et al, 2021 ; Luo L. et al, 2022 ), glucose metabolism ( Gao et al, 2020 ; Li L. et al, 2022 ; Luo L. et al, 2022 ; Ma Q. et al, 2022 ), glycolysis ( Feichtinger et al, 2017 ; Zhou et al, 2021 ; Li L. et al, 2022 ), bile acids ( Alizadeh and Raufman, 2022 ; Jian et al, 2022 ; Yin et al, 2022 ; Yuan et al, 2022 ) and other aspects. The intracerebral glucose metabolism and glycolysis, which produced the major donor substrate for O-GlcNAcylation ( Liu X. et al, 2021 ), were regulated directly by intestinal microbiota and their metabolites.…”
Section: Discussionmentioning
confidence: 87%
“…This reduction exacerbates the progression of gastric cancer, resulting in shortened survival rates for patients diagnosed with the disease (Rahman et al, 2020). The research by Rahman (Rahman et al, 2020) and Noto (Alizadeh and Raufman, 2022) iron deficiency contributes to gastric carcinogenesis through the induction of gastric inflammation, thereby promoting disease progression. However, some scholars have also identified a significant direct correlation between increased heme iron intake (>3.14 mg/day) and the risk of distal gastric cancer (Epplein et al, 2014).…”
Section: Ironmentioning
confidence: 99%